2012
DOI: 10.3945/an.111.001784
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and the Nervous System: An Overview of its Actions

Abstract: The role of vitamin K in the nervous system has been somewhat neglected compared with other physiological systems despite the fact that this nutrient was identified some 40 y ago as essential for the synthesis of sphingolipids. Present in high concentrations in brain cell membranes, sphingolipids are now known to possess important cell signaling functions in addition to their structural role. In the past 20 y, additional support for vitamin K functions in the nervous system has come from the discovery and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 69 publications
2
139
0
15
Order By: Relevance
“…S4 A-C), did not cause neuronal degeneration in vivo in nontransgenic littermates with an intact BSCB (Fig. 3 D-F), and did not interfere with the vitamin K-dependent synthetic pathway (29) as shown by normal levels of sphingolipids or Gas6 in spinal cord (Fig. S4 G and H).…”
Section: Significancementioning
confidence: 85%
“…S4 A-C), did not cause neuronal degeneration in vivo in nontransgenic littermates with an intact BSCB (Fig. 3 D-F), and did not interfere with the vitamin K-dependent synthetic pathway (29) as shown by normal levels of sphingolipids or Gas6 in spinal cord (Fig. S4 G and H).…”
Section: Significancementioning
confidence: 85%
“…Dietary K2 is processed in the liver and released into the circulation via high and low density lipoproteins that make them readily available for uptake into extrahepatic tissues [36][37][38]. Fermented foods such as cheese have significantly higher levels of K2 than milk.…”
Section: A Summary Of the Features Of Vitamin K2mentioning
confidence: 99%
“…The risk of dementia associated with the low levels of vitamin B12 and folic acid, it has been greater also in subjects with good cognitive basic functions. There is a convincing evidence that vitamin K has important actions in the nervous system as a unique cofactor to the y-glutamyl carboxylase enzyme; vitamin K contributes to the biological activation of proteins Gas6 and protein S, ligands for the receptor tyrosine kinases of the TAM family (Tyr03, Axl, and Mer) (33). It has been suggested that vitamin K may have an effect on neuronal damage and that supplementation can lead benefit for the treatment of this disease.…”
Section: Vitamins: Focus On B12 B9 C K Dmentioning
confidence: 99%